Evaluation of the Schistosoma mansoni Y-box-binding protein (SMYB1) potential as a vaccine candidate against schistosomiasis - Dias, Silvia R.; Boroni, Mariana; Rocha, Elizângela A.; Lüscher-Dias, Thomaz; Laet-Souza, Daniela; Oliveira, Fabricio M.; Bitar, Mainá; Macedo, Andréa M.; Machado, Carlos R.; Caliari, Marcelo V.; Franco, Gloria R. (Frontiers in Genetics, 2014)
Schistosomiasis is a neglected tropical disease, and after malaria, is the second most important tropical disease in public health. A vaccine that reduces parasitemia is desirable to achieve mass treatment with a low cost. Although potential antigens have been identified and tested in clinical trials, no effective vaccine against schistosomiasis is available. Y-box-binding proteins (YBPs) regulate gene expression and participate in a variety of cellular processes, including transcriptional and translational regulation, DNA repair, cellular proliferation, drug resistance and stress responses. The Schistosoma mansoni ortholog of the human YB-1, SMYB1, is expressed in all stages of the parasite life cycle. Although SMYB1 binds to DNA or RNA oligonucleotides, immunohistochemistry assays demonstrated that it is primarily localized in the cytoplasm of parasite cells. In addition, SMYB1 interacts with a protein involved in mRNA processing, suggesting that SMYB1 functions in the turnover, transport and/or stabilization of RNA molecules during post-transcriptional gene regulation. Here we report the potential of SMYB1 as a vaccine candidate. We demonstrate that recombinant SMYB1 stimulates the production of high levels of specific IgG1 antibodies in a mouse model. The observed levels of specific IgG1 and IgG2a antibodies indicate an actual protection against cercariae challenge. Animals immunized with rSMYB1 exhibited a 26% reduction in adult worm burden and a 28% reduction in eggs retained in the liver. Although proteins from the worm tegument are considered optimal targets for vaccine development, this study demonstrates that unexposed cytoplasmic proteins can reduce the load of intestinal worms and the number of eggs retained in the liver.